Odpowiedź :
Odpowiedź:
a)
4x - 6 = 26 /+6
4x = 32 / :4
x = 8
Spr.
L = 4*8 - 6 = 32 - 6 = 26
P = 26
L = P
b)
4 + 3x = 28 /-4
3x = 24 /:3
x = 8
Spr.
L = 4 + 3*8 = 4 + 24 = 28
P = 28
L = P
c)
5x - 8 = 27 / +8
5x = 35 /:5
x = 7
Spr.
L = 5*7 - 8 = 35 - 8 = 27
P = 27
L = P
d)
3y + 4 = 19 /-4
3y = 15 /:3
y = 5
Spr.
L = 3*5 + 4 = 15 + 4 = 19
P = 19
L = P
e)
2 + 7a = 44 /-2
7a = 42 /:7
a = 6
Spr.
L = 2 + 7*6 = 2+42 = 44
P = 44
L = P
f)
2t - 13 = 1 /+13
2t = 14 /:2
t = 7
Spr.
L = 2*7 - 13 = 14-13 = 1
P = 1
L=P
g)
4x - 8 = 12 / +8
4x = 20 /:4
x = 5
Spr.
L = 4*5 - 8 = 20 - 8 = 12
P = 12
L=P
h)
2y + 10 = 2 / -10
2y = -8 /:2
y = -4
Spr.
L = 2*(-4) + 10 = -8 + 10 = -2
P = 2
L = P
i)
5 - 6x = -13 / -5
-6x = -18 /:(-6)
x = 3
Spr.
L = 5 - 6*3 = 5 - 18 = 13
P = 13
L = P
j)
9x - 12 = 6 / +12
9x = 18 /:9
x = 2
Spr.
L = 9*2 - 12 = 18 -12 = 6
P = 6
L = P
k)
7x - 14 = 14 / +14
7x = 28 /:7
x = 4
Spr.
L = 7*4 - 14 = 28 - 14 = 14
P = 14
L = P
l)
5a - 2 = 23 / +2
5a = 25 / :5
a = 5
Spr.
L = 5*5 - 2 = 25 - 2 = 23
P = 23
L = P
m)
6x + 4 = 9 /-4
6x = 5 / :6
x = [tex]\frac{5}{6}[/tex]
Spr.
L = 6*[tex]\frac{5}{6}[/tex] + 4 = 4 + 4 = 9
P = 9
L = P
n)
[tex]\frac{3}{4}[/tex] + 5x = 4,75 /-[tex]\frac{3}{4}[/tex]
5x = 4 /:5
x = [tex]\frac{4}{5}[/tex]
Spr.
L = [tex]\frac{3}{4}[/tex] + 5*[tex]\frac{4}{5}[/tex] = [tex]\frac{3}{4}[/tex] + 4 = 4[tex]\frac{3}{4}[/tex]
P = 4,75
L = P
o)
[tex]\frac{1}{6}[/tex]t - 7 = 1 / +7
[tex]\frac{1}{6}[/tex]t = 8 /*[tex]\frac{6}{1}[/tex]
t = 48
Spr.
L = [tex]\frac{1}{6}[/tex]*48 - 7 = 8 - 7 = 1
P = 1
L = P